Organization of Production and Business Processes in Value Chains Based on Applied Scenarios for the Digitalization of Enterprises - Yu. F. Telnov; A. A. Bryzgalov; D. S. Koroleva (Открытое образование (Москва))
The purpose of the research. The implementation of end-to-end digital technologies into the economic activities of enterprises radically changes the organization of production and business processes within the framework of more efficient business models. As a result, new application scenarios are formed that determine the changing structure of production and business processes and the emergence of new roles of participants in the value chain. From this point of view, the article aims to develop and substantiate methods for constructing production and business processes for various types of business models based on modern digital technologies.Research methods. The paper discusses the principles and uses methods for identifying, classifying and constructing production and business processes for various application scenarios of digitalization of manufacturing enterprises. The methods of identification and classification of production and business processes are based on the definition of the stages of the product life cycle and the provision of services considered in the Reference Architectural Model Industrie 4.0 (RAMI). The proposed methods of constructing production and business processes are based on the use of digital platforms, digital twins (software administrative shells), methods of collecting and processing big data. For the selected types of production and business processes, an approach is proposed to describe the features of their implementation from the perspective of various application scenarios of digitalization. When constructing the structure of production and business processes, role models of interaction of participants in value chains are used.Results. This paper presents the classification of production and business processes in accordance with the Reference Architectural Model Industrie 4.0 (RAMI), which highlights the innovative processes of product creation and service provision, production and supply chain processes, as well as asset management processes of enterprises. The analysis of various application scenarios for the selected classes of production and business processes was carried out, which made it possible to link these scenarios with the most common types of business models of digital enterprises. The role model of interaction of participants in the value chain has been clarified for the most common application scenario associated with the use of value-based services (VBS), which allows the accumulation and processing of generated digital data on the performance of physical assets at the operational, tactical and strategic management levels.Conclusion. The developed methods of identification, classification and construction of production and business processes based on a scenario approach to the use of digital technologies and role modeling in the processes of interaction of participants in the value chain are aimed at improving the efficiency of creating and using business models of enterprises digital transformation.